2016
DOI: 10.1007/s10530-016-1239-6
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy of a native grassland community as a potential mechanism of resistance against invasion by introduced plants

Abstract: Successful plant invasions depend, at least partly, on interactions between introduced plants and native plant communities. While allelopathic effects of introduced invaders on native resident species have received much attention, the reverse, i.e. allelopathic effects of native residents on introduced plants, have been largely neglected. Therefore, we tested whether allelopathy of native plant communities decreases their invasibility to introduced plant species. In addition, we tested among the introduced spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 57 publications
(77 reference statements)
3
33
0
Order By: Relevance
“…Some evidence has suggested that allelopathic native plants play a role in inhibiting the growth of invaders [37][38][39]. We found that the allelopathic activity in natural forest soil and litter inhibited the growth of P. americana but that RP soil promoted its growth (Figures 2 and 3), which seems to confirm our second hypothesis: Allelopathy of natural forests inhibits P. americana growth and that of the R. pseudoacacia plantation promotes its growth.…”
Section: The Effects Of Allelopathy On Plant Growthsupporting
confidence: 86%
See 2 more Smart Citations
“…Some evidence has suggested that allelopathic native plants play a role in inhibiting the growth of invaders [37][38][39]. We found that the allelopathic activity in natural forest soil and litter inhibited the growth of P. americana but that RP soil promoted its growth (Figures 2 and 3), which seems to confirm our second hypothesis: Allelopathy of natural forests inhibits P. americana growth and that of the R. pseudoacacia plantation promotes its growth.…”
Section: The Effects Of Allelopathy On Plant Growthsupporting
confidence: 86%
“…Similarly, Hou et al [39] found that monsoon evergreen broadleaf forest soil has strong allelopathic activity towards invasive plants in lower subtropical China. Ning et al [37] provided evidence that in grassland communities allelopathic native grasses increased community resistance to introduced plants. However, this study did not produce results for succession-associated allelopathy consistent with Hou et al [39], who found that late-successional stage forest soils have stronger allelopathy than early-successional stages.…”
Section: The Effects Of Allelopathy On Plant Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In both the survival and biomass models, we included epiphyte species, severance, removal and their two-and three-way interactions as fixed terms. We accounted for differences in initial size of the epiphyte ramets by including initial size (frond length) as a covariate in the model (Ning et al, 2016). Furthermore, we accounted for variation among host species and host trees (treeID) by including them as random terms, with individual host trees nested within host species.…”
Section: Measurements and Analysesmentioning
confidence: 99%
“…However, the resident plants may also produce allelopathic compounds, and it could be that allelopathy of resident plants provides resistance against invaders (Weidenhamer and Romeo 2005). Although this idea was already posed by Rabotnov (1982), it has rarely been tested (Cummings et al 2012;Hou et al 2012;Ning et al 2016;van Kleunen et al 2018).…”
Section: Introductionmentioning
confidence: 99%